Examining the knowledge, attitudes, and implementation of evidence-based practice among nurses in the United Arab Emirates: a national cross-sectional descriptive study - Mohammed Alblooshi , Sumaya; H. R. Hijji , Farha; Abdul Razzak , Hira; Ahmad Mohammad Wishah , Moayad; Alkarbi, Mubarkah; Zaid Harbi , Alya (International Journal Of Community Medicine And Public Health, 2023)
Background: Evidence-based practice across United Arab Emirates has been widely adopted as country strategic direction but the knowledge, attitudes, and its implementation among nurses are yet to be explored. This study explored the knowledge, attitude and implementation of EBP among nurses working in the UAE. Methods: A cross-sectional survey was conducted from 1,602 nurses working in different healthcare settings across the UAE. Two tools were used in the survey for data collection: the self-reported EBP Questionnaire created by Upton and the EBP Implementation scale by Melnyk, Fineout-Overholt, and Mays. Results: A total of 1602 nurses (response rate: 95.9%) completed the questionnaire. The mean age was 38.7 years (age range=20-60 years). The study found that the majority of participants were female (84.1%), with 39.6% being staff nurses and the largest group (28.2%) having 11-15 years of nursing experience. Attitudes towards EBP showed the highest mean score of 4.93±1.7 followed by knowledge (4.5±1.4) and practice (3.92±1.7). Hence, the nurses’ attitudes towards EBP appeared to be positive, their implementation and knowledge were comparatively moderate. The total EBPQ score was found to be 106.3 out of 168. Conclusions: The study’s finding can be used as a starting point for future evaluations and the development of strategies to encourage EBP utilization among nurses in the UAE. Establishing academic and professional development programs for EBP is necessary for organizations and nursing leaders. Combining EBP education with mentor support can encourage nurses to engage in clinical practice informed by the best available evidence.